2012
DOI: 10.1039/c2lc40564d
|View full text |Cite
|
Sign up to set email alerts
|

Visual and high-throughput detection of cancer cells using a graphene oxide-based FRET aptasensing microfluidic chip

Abstract: Rapid and efficient measurement of cancer cells is a major challenge in early cancer diagnosis. In the present study, a miniature multiplex chip was created for in situ detection of cancer cells by implementing a novel graphene oxide (GO)-based Förster resonance energy transfer (FRET) biosensor strategy, i.e. assaying the cell-induced fluorescence recovery from the dye-labeled aptamer/graphene oxide complex. Fluorescence intensity measurement and image analyses demonstrated that this microfluidic biosensing me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…The linear detection range was 0.09-09U/mL and the detection limit was calculated to be 0.00132U/mL. In the same manner, Cai et al In this FRET assay, FAM-modified Sgc8 aptamer was a donor and GO was used as a quencher (Cao et al, 2012). GO was firstly modified on the base of microfluidic channels.…”
Section: Liu Et Al Reported a Homogeneous Fret Sensing Platform Basementioning
confidence: 99%
“…The linear detection range was 0.09-09U/mL and the detection limit was calculated to be 0.00132U/mL. In the same manner, Cai et al In this FRET assay, FAM-modified Sgc8 aptamer was a donor and GO was used as a quencher (Cao et al, 2012). GO was firstly modified on the base of microfluidic channels.…”
Section: Liu Et Al Reported a Homogeneous Fret Sensing Platform Basementioning
confidence: 99%
“…Most of the GO-based FRET sensors to date use DNA-based molecular recognition, in the form of molecular beacons, aptamers, or DNAzymes, for the specific detection of a range of target analytes from small molecules, such as heavy metals and mycotoxins, to proteins including thrombin, DNA, and even whole cancer cells [170][171][172][173][174][175]. Donor species range from traditional organic fluorophores to QDs and upconverting NPs (UCNPs); the diversity reflects the superquenching abilities of the GO materials.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…At the same time, the dye molecule also leaves the GO surface and the fluorescence of the dye recovers. By employing this concept, early studies on this type of sensor have demonstrated DNA sensors (i.e., sensors for complementary DNA) [11][12][13][14][15][16] and aptasensors in an aqueous dispersion of GO [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 98%